THE CALCIUM LOOPING CYCLE STUDY FOR CAPTURING CARBON DIOXIDE APPLIED TO THE ENERGY GENERATION - Ávila, I.; Mortari, A.; Santos, A. M.; Crnkovic, P. M. (Revista de Engenharia Térmica, 2013)
The calcium looping process (Ca-L) is a promising technology to reduce of the carbon dioxide (CO2) emissions when applied in energy generation systems. Ca-based materials (usually limestone) are used in this process as CO2 sorbents. Thus, the CO2 capture occurs by the reversible reaction between calcium oxide (CaO) and CO2, resulting in the calcium carbonate form (CaCO3). Compared to other technologies applied to carbon sequestration process, the Ca-L offers additional advantages such: the use of fluidized bed technology that is already well established; this process occurs at high temperature, and the excess of heat generated can be recovered; the cost of limestone sorbents is low because of its wide availability. However, in the applying the Ca-L process is essential to understand the mechanism and the effect of partial pressure of CO2 in both, calcination and carbonation processes; to investigate the effect of sintering and to evaluate the sorbent activity decay. In this paper, empirical technique such as thermogravimetry is applied to investigate the reactivity of dolomite as CO2 sorbent. The effect of CO2 high concentrations in both calcination/carbonation processes is also investigated.